2000
DOI: 10.1098/rspb.2000.1120
|View full text |Cite
|
Sign up to set email alerts
|

Hot spots, indicator taxa, complementarity and optimal networks of taiga

Abstract: If hot spots for different taxa coincide, priority-setting surveys in a region could be carried out more cheaply by focusing on indicator taxa. Several previous studies show that hot spots of different taxa rarely coincide. However, in tropical areas indicator taxa may be used in selecting complementary networks to represent biodiversity as a whole. We studied beetles (Coleoptera), Heteroptera, polypores or bracket fungi (Polyporaceae) and vascular plants of old growth boreal taiga forests. Optimal networks fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 25 publications
1
33
1
1
Order By: Relevance
“…Nevertheless, their inclusion in conservation planning and management is important because of their vital functional roles in ecosystems (Lodge et al 2004, Öster 2008, McMullan-Fisher et al 2009) and their great richness estimated worldwide (Hawksworth 2001). However, while at large spatial scales communities with high tree-species richness have been found to have correspondingly high macrofungal species richness (Schmit et al 2005), low correlations have been found at local scales (e.g., Virolainen et al 2000, Saetersdal et al 2003, Similä et al 2006, Santi et al 2010.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, their inclusion in conservation planning and management is important because of their vital functional roles in ecosystems (Lodge et al 2004, Öster 2008, McMullan-Fisher et al 2009) and their great richness estimated worldwide (Hawksworth 2001). However, while at large spatial scales communities with high tree-species richness have been found to have correspondingly high macrofungal species richness (Schmit et al 2005), low correlations have been found at local scales (e.g., Virolainen et al 2000, Saetersdal et al 2003, Similä et al 2006, Santi et al 2010.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the possibility of high congruence between different taxa, which is extremely interesting from an ecological viewpoint, can reduce the time and costs necessary for planning conservation actions, although no single biotic group shows a perfect match with any other. The "taxon surrogacy" hypothesis (Ryti 1992) is based on the assumption of concordance among species richness or patterns of community composition across different taxonomic groups (Virolainen et al 2000, Su et al 2004. Nevertheless, the selection of surrogate taxonomic groups is not straightforward, and different methods have been applied by various authors.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Gómez-Hernández and Williams-Linera (2011) reported a negative correlation between macrofungi and overstorey tree richness. Simulation studies (Virolainen et al 2000;Chiarucci et al 2005;McMullan-Fisher et al 2010) showed that site-selection optimised based on plant communities cannot maximize fungal diversity, even if there is a statistical relationship between the compositions of the two groups. In studies by Virolainen et al (2000) and McMullanFisher et al (2010), random selection performs better than selection based on plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation studies (Virolainen et al 2000;Chiarucci et al 2005;McMullan-Fisher et al 2010) showed that site-selection optimised based on plant communities cannot maximize fungal diversity, even if there is a statistical relationship between the compositions of the two groups. In studies by Virolainen et al (2000) and McMullanFisher et al (2010), random selection performs better than selection based on plant species. Several factors may underlie these contradictory results: (1) the studies were performed at different scales (Flather et al 1997) (from continental scale meta-analysis to comparing degradation stages of the same vegetation type); (2) different fungal groups may respond differently to environmental factors and may correlate with different proxies (cf.…”
Section: Introductionmentioning
confidence: 99%
“…los primeros se han usado para inferir la riqueza de organismos más problemáticos de inventariar debido, entre otras razones, a su pequeño tamaño o a su desconocimiento taxonómico (Di Castri et al, 1992;Halffter y Favila, 1993;Gaston, 1996;Margules y Pressey, 2000;Jayasuriya y Abayawardana, 2008). el uso de estos grupos para ubicar áreas de conservación cuenta con una literatura amplia y entre los taxones que se han empleado al respecto están: i) artrópodos (arañas e insectos; Virolainen et al, 2000;Cardoso et al, 2004;Finch y Löffler, 2010), ii) hongos (Basidiomicetes; Virolainen et al, 2000), iii) mariposas (Papilionidae; Fleishman et al, 2005), iv) plantas (árboles; Villaseñor et al, 2003;Schmit et al, 2005) con respecto a los métodos iterativos, éstos priorizan sitios para la conservación de la biodiversidad con base en la importancia relativa del número de especies, evaluando su grado de complementaridad y qué tan particulares son con respecto a los taxones que albergan, además que permiten considerar las restricciones que puedan tener ciertas áreas para ser conservadas y ser flexible en cuanto a las opciones que pueden aportar, lo que incrementa su eficiencia y representatividad (Margules et al, 1994(Margules et al, , 2002Margules y Pressey, 2000;Ceballos, 2007). la porción occidental de méxico presenta áreas con escaso conocimiento biológico, a pesar de formar parte de mesoamérica, una de las regiones más importantes a nivel mundial por la biodiversidad que alberga (Myers et al, 2000;Olson y Dinerstein, 2002).…”
Section: Introductionunclassified